Elevated symptoms of depression and anxiety among family members and friends of critically ill COVID-19 patients – an observational study of five cohorts across four countries - Lovik, Anikó; González-Hijón, Juan; Hoffart, Asle; Fawns-Ritchie, Chloe; Magnúsdóttir, Ingibjörg; Lu, Li; Unnarsdóttir, Anna Bára; Kähler, Anna K.; Campbell, Archie; Hauksdóttir, Arna; Chourpiliadis, Charilaos; McCartney, Daniel L.; et al. (The Lancet Regional Health - Europe, 2023)
Background : Little is known regarding the mental health impact of having a significant person (family member and/or close friend) with COVID-19 of different severity. Methods : The study included five prospective cohorts from four countries (Iceland, Norway, Sweden, and the UK) with self-reported data on COVID-19 and symptoms of depression and anxiety during March 2020–March 2022. We calculated prevalence ratios (PR) of depression and anxiety in relation to having a significant person with COVID-19 and performed a longitudinal analysis in the Swedish cohort to describe temporal patterns. Findings : 162,237 and 168,783 individuals were included in the analysis of depression and anxiety, respectively, of whom 24,718 and 27,003 reported a significant person with COVID-19. Overall, the PR was 1.07 (95% CI: 1.05–1.10) for depression and 1.08 (95% CI: 1.03–1.13) for anxiety in relation to having a significant person with COVID-19. The respective PRs for depression and anxiety were 1.15 (95% CI: 1.08–1.23) and 1.24 (95% CI: 1.14–1.34) if the patient was hospitalized, 1.42 (95% CI: 1.27–1.57) and 1.45 (95% CI: 1.31–1.60) if the patient was ICU-admitted, and 1.34 (95% CI: 1.22–1.46) and 1.36 (95% CI: 1.22–1.51) if the patient died. Individuals with a significant person with hospitalized, ICU-admitted, or fatal COVID-19 showed elevated prevalence of depression and anxiety during the entire year after the COVID-19 diagnosis. Interpretation : Family members and close friends of critically ill COVID-19 patients show persistently elevated prevalence of depressive and anxiety symptoms.